'They call us for everything': cynicism, rural policing and youth justice. (3rd July 2022) - Spencer, Dale; Ricciardelli, Rose; Silva, Derek
ABSTRACT: While researchers have studied police cynicism in urban contexts, few have studied cynicism in relation to rural policing and even less in relation to police responses to young people in these settings. In the current article, we respond by addressing the complex ways cynicism manifests in the rural policing of young people. Based on 104 semi-structured interviews and focus groups ( n  = 31) with 134 rural police officers in Atlantic Canada, we demonstrate that cynicism manifests in rural policing as role confusion, in relation to recalcitrant young people, the lack of organisational support, inefficacy of youth justice systems, and insufficient support from parents of young people in conflict with the law. Our findings highlight the value of community and organisational support, resources, and trust that are particularly salient in rural settings.